Measuring outcomes for dysphagia: validity and reliability of the European Portuguese eating assessment Tool (P-EAT-10) - Nogueira, D. S.; Ferreira, P. L.; Reis, E. A.; Lopes, I. S. (Dysphagia, 2015)
The purpose of this study was to evaluate the validity and the reliability of the European Portuguese version of the EAT-10 (P-EAT-10). This research was conducted in three phases: (i) cultural and linguistic adaptation; (ii) feasibility and reliability test; and (iii) validity tests. The final sample was formed by a cohort of 520 subjects. The P-EAT-10 index was compared for socio-demographic and clinic variables. It was also compared for both dysphagic and non-dysphagic groups as well as for the results of the 3Oz wst. Lastly, the P-EAT-10 scores were correlated with the EuroQol Group Portuguese EQ-5D index. The Cronbach’s ? obtained for the P-EAT-10 scale was 0.952 and it remained excellent even if any item was deleted. The item-total and the intraclass correlation coefficients were very good. The P-EAT-10 mean of the non-dysphagic cohort was 0.56 and that of the dysphagic cohort was 14.26, the mean comparison between the 3Oz wst groups and the P-EAT-10 scores were significant. A significant higher perception of QoL was also found among the non-dysphagic subjects. P-EAT-10 is a valid and reliable measure that may be used to document dysphagia which makes it useful both for screening in clinical practice and in research.